Histories of migrant knowledge transatlantic and global perspectives - Westermann, Andrea; Erdur, Onur 1984- (Bulletin of the German Historical Institute Supplement, 2020)
Our GHI Bulletin Supplement adds to this ongoing discussion about the histories of migrant knowledge. The contributors are scholars of migration history who participated in workshops or panels hosted by the Pacific Regional Office of the German Historical Institute of Washington DC in 2018. We asked them to take a significant point, principle, methodological consideration, or concrete analysis from their own work testing a history of knowledge approach. Whereas each case study presents a unique perspective, their juxtaposition in this volume, and particularly their groupings, illuminate what they have in common and enrich the analyses, as we elucidate below after summarizing the individual contributions. With this collection of articles, we hope to spark further research into the epistemic dynamics of displacement, into alternative sites of migrant knowledge production, and into overlooked repositories of migrant knowledge.